Analysis of The Benefits of Financial Technology and Financial Socialization Towards Financial Behavior in Students in Surabaya Post Pandemic with Financial Literacy as The Intervening Variable - Wirawan Dwi Radianto; Angelina Suryanto (UNUSA Press, 2023)
The purpose of this study is to investigate financial behavior among university students in Surabaya and analyze the relationship between perceived usefulness of financial technology, financial socialization, and financial literacy as an intervening variable. Conclusive causality research is used for this research with primary data collected from questionnaires. The sampling techniques used a combination of proportional stratified random sampling and purposive sampling towards 466 university students from 6 universities in Surabaya. Data analyzed using Partial Least Squares - Structural Equation Model (PLS-SEM) techniques. The result shows that financial literacy and financial socialization positively impacts financial behavior while perceived usefulness of financial technology variables does not affect financial behavior. Mediation results showsthat financial literacy is able to mediate perceived usefulness of financial technology and financial socialization towards financial behavior of university students in Surabaya. Through this research is expected to be the reference for various parties, especially for curriculum makers to consider optimization technical teaching strategies and assessment indicators in basic financial outreach.